A pedagogical model to deconstruct moving pictures in virtual learning environments and its impact on the self-concept of postgraduate students - Moreira, J. António (2017)
The vertiginous evolution of information and communication technologies (ICT) and the advent of the Internet propitiated the emergence of a networked society marked by deep changes in the economy, stimulating the emergence of new paradigms, models, educational communication processes and new learning scenarios. It is precisely one of these models – a pedagogical model to deconstruct moving pictures –, that we intend to analyze, describing its impact on the academic self-concept of twenty-four graduate students, based on the qualitative analysis of their own perceptions and narratives. The results show that these pedagogical model environments – whose design is anchored in the principles of socio-constructivism, collaborative learning, autonomy, flexibility and interaction – may have very positive effects on the academic self-concept of higher education students in the various dimensions taken into consideration: Motivation, task Orientation, Confidence in their own capacities and Relationship with colleagues.